Screening of moth bean (Vigna aconitifolia) core collection against yellow mosaic virus - MEGHWAL, R R; JOSHI, UMA; KUMAR, SUSHIL; SHARMA, R (The Indian Journal of Agricultural Sciences, 2015)
A core collection of moth bean [Vigna aconitifolia (Jacq) Marechal] germplasm, consisting of 204 lines identified in NAIP project was evaluated for mung bean yellow mosaic virus (MYMV) resistance; most of the lines were totally destroyed by yellow mosaic virus. Out of 204 accessions, 13 exhibited resistance/tolerance to disease in terms of intensity or level of symptoms appearing on individual plants. The susceptible lines could not bear flowers while resistant plants produced reasonable yield. The response of germplasm to MYMV exposed a distinct variation to the disease reaction. No genetic association between qualitative traits (seed color, leaf shape and plant type) and resistance/susceptibility to MYMV was observed in the present study. However, seed yield was significantly reduced with increased disease intensity.